Maternal Mortality. 4 years experience in the National Hospital Cayetano Heredia - Díaz Herrera, Jorge (2015)
OBJECTIVE.- To determine the variation in type of maternal death and associated pathologies. MATERIAL AND MÉTHODS: Retrospective descriptive case series study, including all maternal deaths occurring at Cayetano Heredia National Hospital from 1998 through 2001. RESULTS: Twelve thousand four hundred and forty tour living newborns and 14 maternal deaths were registered with a maternal mortality rate of 112,5 by 100 living newborn. The main type of maternal death was the indirectwith 57, 1 % (Scases) and the main pathology associated was acquired immune deficiency syndrome (AIDS) in 21,4% (3 cases). The direct maternal deaths represented 42,9% (6 cases). In the last two years just one direct maternal death by eclampsia has occurred as well as 5 cases of indirect maternal deaths, 3 due to AIDS. CONCLUSION.- The type of maternal death showed an irregular behavior with a descending tendency in direct causes and increment in the indirect ones.